Compendium of recent studies on tourism development (OAS WashingtonUS, 1993)
Deals with problems affecting the tourism industry in Latin America and the Caribbean. Looks at issues such as the need to enhance the net economic benefit from tourism; conservation of the environment and tourism; collaboration of the cruise industry with other segments of the tourism sector; integration of tourism attractions in bordering countries; and the attraction of additional sources of concessionary financing for tourism projects.
DC